2014
DOI: 10.1080/1369183x.2014.948392
|View full text |Cite
|
Sign up to set email alerts
|

State-assisted Highly Skilled Return Programmes, National Identity and the Risk(s) of Homecoming: Israel and Germany Compared

Abstract: State-assisted return programmes (SARPs) have emerged as key components of diaspora mobilisation strategies in countries of origin. Especially in countries where the principle of jus sanguinis underpins citizenship regimes, these programmes have often been drawn from ostensibly national(istic) discourses in order to encourage the repatriation of (mostly highly skilled) citizens residing abroad. Drawing on interviews with public officials and migrants as well as content analysis of primary and secondary materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Others may be troubled by the changing political climate in their countries of birth, including rising national(istic) sentiments. Cohen and Kranz [31], for example, conclude that some departing Israeli scientists are concerned with the country’s political and religious radicalization and their German counterparts ‘often feel as national misfits’ (p. 806). Other structural and circumstantial factors, including immigration policy in destination countries, macroeconomic conditions or increasing racism also stimulate academic outmigration [32].…”
Section: Academic Mobilitymentioning
confidence: 99%
“…Others may be troubled by the changing political climate in their countries of birth, including rising national(istic) sentiments. Cohen and Kranz [31], for example, conclude that some departing Israeli scientists are concerned with the country’s political and religious radicalization and their German counterparts ‘often feel as national misfits’ (p. 806). Other structural and circumstantial factors, including immigration policy in destination countries, macroeconomic conditions or increasing racism also stimulate academic outmigration [32].…”
Section: Academic Mobilitymentioning
confidence: 99%
“…The German Academic International Network aims at attracting German scientists in North America by offering job placement assistance and research funding. The German Scholars Organizations funded up to 100,000 Euros to German universities to help them attract and hire German scholars back home (Cohen and Kranz, ). However, diaspora recruitment policies are not only more widely used by Global South countries (Hooper and Sumption, ) than by those in the Global North, but also in some cases they present the only policy alternative to attract highly‐skilled in‐migrants.…”
Section: Conceptual Considerationsmentioning
confidence: 99%
“…Cumbersome administration was also important for educated African migrants, who quoted its negative effects on their already high levels of mistrust towards governments in their countries of origin (Bach, ). Discomfort with the system's so‐called ‘lack of transparency’ and ‘culture of work’ at home‐based institutions, including public universities, has also been recorded among potential returnees to other more developed countries, such as Germany (Cohen & Kranz, ) and Italy (Foadi, ).…”
Section: Return Migration As a State Strategymentioning
confidence: 99%
“…In Israel, studies on return migration have shown a complex pattern, with returnees reporting a mixture of familial-personal and identity-related determinants on the one hand as well as more professional-economic ones on the other (Lev Ari, 2006). A recent comparative study 292 N. Cohen of Israeli and German SARPs confirms that highly skilled Israeli migrants who consider repatriation are concerned with the country's limited professional options and notoriously high living expenses (Cohen & Kranz, 2014). However, they also contend that highly educated professionals are equally worried about the political and religious radicalisation in Israel.…”
Section: Return Migration As a State Strategymentioning
confidence: 99%